2020
DOI: 10.1002/jsfa.10483
|View full text |Cite
|
Sign up to set email alerts
|

Safety assays and nutritional values of mycoprotein produced by Fusarium venenatum IR372C from date waste as substrate

Abstract: BACKGROUNDNutritional and environmental benefits of mycoprotein verify its beneficial role on the health of humankind in the next decades. Agro‐industrial wastes can be used as cheap substrates to decrease the total cost of product. However, fungi may produce toxins or lead to allergic reactions in consumers. Therefore, the study of the safety and nutritional aspects of this product are very important.RESULTSFusarium venenatum IR372C was cultured on date wastes and ammonium salts in submerge fermentation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…Agri-food wastes can potentially be utilized as a nutrient source in the production of mycoprotein. In one study, date wastes were used as a fermentation substrates for F. venenatum, and the authors found that the resulting mycoproteins did not result in allergic reactions in tested human subjects, that there was an absence of fumonisin gene expression in the starter culture and that no mycotoxins (zearalenone and deoxynivalenol) were detected in the fermentation medium, although low levels of lead (658 µg/kg), arsenic (161 µg/kg) and cadmium (30.57 µg/kg) were reported [187]. Future research can aim at assessing other waste materials for their potential use in mycoprotein production.…”
Section: Fungal Protein (Mycoprotein): Quorn Tm Potential Allergens ...mentioning
confidence: 98%
“…Agri-food wastes can potentially be utilized as a nutrient source in the production of mycoprotein. In one study, date wastes were used as a fermentation substrates for F. venenatum, and the authors found that the resulting mycoproteins did not result in allergic reactions in tested human subjects, that there was an absence of fumonisin gene expression in the starter culture and that no mycotoxins (zearalenone and deoxynivalenol) were detected in the fermentation medium, although low levels of lead (658 µg/kg), arsenic (161 µg/kg) and cadmium (30.57 µg/kg) were reported [187]. Future research can aim at assessing other waste materials for their potential use in mycoprotein production.…”
Section: Fungal Protein (Mycoprotein): Quorn Tm Potential Allergens ...mentioning
confidence: 98%
“…In the last decade, mycoproteins have emerged as an environmentally friendly and cheap source, since it can be synthetised with agronomical by-products and its carbon footprint is, at least, 10 times lower than traditional meats (73). Furthermore, mycoproteins appeared not to be potentially allergenic (74) and they could exert benefits related to sports nutrition and cardiometabolic health, such as insulinemia and glycemia attenuation and muscle adaptation (72).…”
Section: Mycoproteinsmentioning
confidence: 99%
“…There is also the risk of toxin production by the organism, absence of which needs to be routinely tested [47]. This could also bring challenges for modifying the SCP production process, as changing the growth substrate or other condition might activate toxin production [49]. Benefits of SCP over traditional animal protein include lower carbon footprint, land use and water consumption and the potential to use industrial food by-products as growth substrate [48,49].…”
Section: Use Of Single Cell Proteins As a Protein Source For Humansmentioning
confidence: 99%
“…This could also bring challenges for modifying the SCP production process, as changing the growth substrate or other condition might activate toxin production [49]. Benefits of SCP over traditional animal protein include lower carbon footprint, land use and water consumption and the potential to use industrial food by-products as growth substrate [48,49]. However, to date SCPs for human consumption are grown using food grade substrates, with associated costs [47].…”
Section: Use Of Single Cell Proteins As a Protein Source For Humansmentioning
confidence: 99%